Propylparaben-induced disruption of energy metabolism in human HepG2 cell line leads to increased synthesis of superoxide anions and apoptosis. (March 2016) - Szeląg, S.; Zabłocka, A.; Trzeciak, K.; Drozd, A.; Baranowska-Bosiacka, I.; Kolasa, A.; Goschorska, M.; Chlubek, D.; Gutowska, I.
Abstract: The effect of propylparaben (in final concentrations 0.4 ng/ml, 2.3 ng/ml and 4.6 ng/ml) on the energy metabolism of HepG2 hepatocytes, superoxide anion synthesis, apoptosis and necrosis is described. Propylparaben can be toxic to liver cells due to the increased production of superoxide anions, which can contribute to a reduced concentration of superoxide dismutase in vivo and impairment of the body's antioxidant mechanisms. Finally, a further reduction in the mitochondrial membrane potential and uncoupling of the respiratory chain resulting in a reduction in ATP concentration as a result of mitochondrial damage may lead to cell death by apoptosis. Highlights: Propylparaben, one of the two most commonly used parabens, can be toxic to liver. The toxicity is associated with the increased production of superoxide anions. An increase in PP concentration is accompanied by a decrease in cellular ATP. Intensification of oxidative stress leads to increased cell death via apoptosis process.